Towards Good Enough Measurement – Sick Leave Statistics as a Case of the Measurement Challenges in Comparative Public Performance. Issue 4 (8th August 2017) - Hoffmann, Cornelia; Dooren, Wouter Van
Abstract: This paper puts forward suggestions on how to deal with typical problems found in international comparisons of governance, illustrated by the case of sick leave statistics. We analysed sick leave data and meta-data of employees in the public administration of six European countries and regions. The purpose of the analysis is to learn about the challenges of and potential solutions for international comparisons of performance. The study demonstrates that problems of reliability and validity can be reduced, provided that sufficient data and meta-data are available. These results suggest that although "perfect comparisons" are difficult to achieve, work can be done to make measurement "good enough".